Analysis on application scenarios and requirements for direct-to-handset LEO satellite - LIU Yue; TIAN Ye; ZHAO Dong; LI Yankun; YANG Huxiao; GAO Ran; XIN Xiangjun (Dianxin kexue)
Direct-to-handset satellite service is one of the important applications for low earth orbiting (LEO) satellite constellation systems. The overview on the main technology routes, application scenarios, and business types of satellite communication service for direct-to-handset was provided. The construction cost, capacity and operating income of LEO satellite constellation system were analyzed. The main applications of direct-to-handset satellite in China should focus on wide coverage and massive connections. Furthermore, there was a risk of commercial closed-loop in high traffic and broadband satellite applications. Finally, the technology trend was discussed associated with application requirements.